Baalbek, Libanon: Forschungen im Steinbruch und die Aufarbeitung der Forschungen von 2001–2012 - van Ess, Margarete (e-Forschungsberichte des DAI, 2023)
In 2013 research work in Baalbek had to be re-organized due to increasing political crises in the wider region. In close cooperation with Lebanese researchers, an excavation in the famous quarry in the south of Baalbek has been carried out aiming at collecting hints for quarrying and transportation techniques for the monumental blocks. Unexpectedly, an even larger block came to light that has to be considered the largest block ever cut in antiquity. Between 2001 and 2011 a comprehensive research project was carried out in Baalbek for the documentation of excavated but not yet published archaeological architectural remains and findings. It aimed at investigating the urban development of the town from its beginning until present. Parts of its results have been published and made public in a WebGIS. In addition, a feasibility study for conservation work has been developed.